Association of folate and vitamin B12 imbalance with adverse pregnancy outcomes among 11,549 pregnant women: An observational cohort study - Yuan, Xiaosong; Han, Xiaoya; Zhou, Wenbo; Long, Wei; Wang, Huiyan; Yu, Bin; Zhang, Bin (Frontiers in Nutrition, 2022)
Abstract Objective: The aim of this study was to evaluate maternal serum levels of folate, vitamin B12 and their ratio on admission for labour and determine whether an imbalance between folate and vitamin B12, represented by a higher or lower serum folate to vitamin B12 ratio (SFVB12R), was associated with adverse pregnancy outcomes. Methods:  A retrospective cohort study of 11, 549 pregnant women attending a district specialized hospital and that had serum folate (SF) and serum vitamin B12 (SVB12) levels measured at delivery was performed. The levels of SF, SVB12, and SFVB12R were defined as high (> 95th percentile), normal (5-95th percentile) and low (< 5th percentile). Information on pregnancy outcomes was retrieved from medical records. Linear regression was performed to examine the association of abnormal SF, SVB12, and SFVB12R levels with fetal growth indicators. Logistic regression was applied to estimate the association between abnormal SF, SVB12, and SFVB12R levels and pregnancy outcomes. Results: Lower SF levels were associated with higher risks of intrahepatic cholestasis of pregnancy (ICP, OR 1.58; 95% CI 1.15-2.17), preeclampsia (PE, OR 1.89; 95% CI 1.28-2.81) and a lower risk of gestational diabetes mellitus (GDM, OR 0.40; 95% CI 0.23-0.70), whereas higher SVB12 levels were associated with higher risk of ICP (OR 2.22; 95% CI 1.67-2.96), PE (OR 1.69; 95% CI 1.04-2.74), and GDM (OR 1.62; 95% CI 1.24-2.11). A higher SFVB12R increased birthweight (β 60.99; 95% CI 29.52-92.45) and was associated with a higher risk of large-for-gestational-age (LGA) newborns (OR 3.08; 95% CI 1.63-5.83); a lower SFVB12R decreased birthweight ( β -43.81; 95% CI -75.62, -12.00) and was associated with a lower risk of LGA newborns (OR 0.75; 95% CI 0.56-1.00), and with higher risks of ICP (OR 2.03; 95% CI 1.54-2.67) and pregnancy induced hypertension (PIH, OR 1.81; 95% CI 1.09-3.00). Conclusion: An imbalance between folate and vitamin B12, represented by a higher or lower SFVB12R before delivery, was significantly associated with adverse pregnancy outcomes (ICP/PIH/LGA).